Flora of the urban parks of the cities of Tegucigalpa and Comayagüela, Honduras - Flores, Ana L. (2022)
Urban parks are places for recreation, rest, and in turn are conservation areas for native species. The objective of this study was to identify the plant species of eight urban parks in Tegucigalpa and Comayagüela of the Department of Francisco Morazán (Honduras), in 2015 and 2022. 102 species were reported in urban parks, belonging to 43 families and 86 genera. The families with the highest number of species were Fabaceae, Asparagaceae, Arecaceae, Euphorbiaceae, Apocynaceae, Bignoniaceae, Myrtaceae and Rutaceae. Trees are the most frequent (48%), followed by shrubs (28%) and herbs (24.5%), of these 56.8% are introduced and 43.2% native. Among the species recorded, Coffea arabica L. and Swietenia humilis Zucc. are listed as endangered according to the IUCN Red List, while Cedrela odorata L., Araucaria heterophylla (Salisb.) Franco and Jacaranda mimosifolia D. Don and 38 species of least concern are listed as vulnerable. Anthropic activities such as destruction, modification, environmental contamination, and lack of maintenance have led to the loss of native vegetation in these urban parks. A proposal for the reintroduction of native species is an alternative to avoid the introduction of plants that can bring with it the incorporation of invasive species.